IMPLEMENTATION OF ZAKAT MANAGEMENT, INFAQ/ALMS THROUGH THE SIMBA APPLICATION TO INCREASE ACCOUNTABILITY AT THE NATIONAL ZAKAT AGENCY (BAZNAS) OF RIAU PROVINCE - Fitriya Wulansari; Bakhtiar , Harkaneri; Mery Agustina Mahmud (UIN Raden Mas Said Surakarta, 2024)
This study aims to determine the Implementations of Zakat Management, Infaq/Donations through the Simba Application to Increase Accountability at the National Amil Zakat Agency (Baznas) Riau Province. The data used in this study were obtained from direct interviews with BAZNAS and documentation. This research was conducted at the National Amil Zakat Agency (BAZNAS) of Riau Province. The method used in this research is qualitative research method with descriptive approach. The results of this study indicate that Baznas Riau Province has implemented the Baznas Management Information System (SIMBA) since 2016 and optimized in 2017. In SIMBA, muzakki and mustahik data are recorded clearly and in detail, as well as incoming and outgoing cash. Baznas Riau Province has won the best SIMBA operator award and the best SIMBA financial report compliance in 2024. They also collaborate with the Ministry of Religious Affairs for training related to PSAK 409. When experiencing problems, Baznas Riau Province directly consults Baznas RI (center), which always responds quickly. From the explanation given, the application of zakat, infaq and sadaqah management in Baznas Riau Province has proven to be very efficient and effective. They have succeeded in achieving zakat management objectives with a high standard of success and an optimal level of effectiveness. SIMBA application becomes a tool to facilitate the decision-making process and policies at the central, provincial, and district/city levels.